Space, Education, and Inclusion Interdisciplinary Approaches - Rißler, Georg; Köpfer, Andreas; Buchner, Tobias (Routledge Research in Education, 2024)
This timely, edited volume brings together interdisciplinary perspectives on space and spatiality in inclusive education discourses. With research from an international range of scholars, the book explores the intersections, boundaries, and intermediary spaces of inclusion and exclusion within educational contexts. It advances thinking in inclusive education research and links discourses of the spatial turn in inclusive education with a call for thinking spatially. Instead of defining one spatial approach as the overarching framework for analysis, it considers the potential of combining spatial approaches from diverse disciplines, including social sciences, educational science, and geography. The book systematically identifies and links the relations between a diversity of spatial theoretical perspectives and phenomena of inclusion/exclusion. This volume provides invaluable, transdisciplinary readings and reflections on space and spatiality in inclusive education, and will be highly relevant for academics, researchers and postgraduate students in the fields of inclusive education, educational theory and the sociology of education.